Existing and proposed ecoregional research in South Asia - Zerbini, E. (International Livestock Research Institute, 1999)
This paper attempts to highlight the major components of an established regional research consortium in South Asia, the operational difficulties, and proposed improvements needed in implementing this regional research. The components and the lessons learned from this mode of research will be very useful when establishing crop-livestock regional research as proposed in the second part of this paper.